Marxism and anthropology: the history of a relationship - Bloch, Maurice (Routledge, 1983)
Examining the writings of Marx and Engels on primitive societies and drawing attention to inconsistencies in their analysis of pre-capitalist societies, this study proceeds to evaluate the anthropological theories of the successors of Marx and Engels as well as linking the controversies concerning anthropology among Marxists and among Soviet anthropologists to the political evolution of Marxism. The book concludes with an exploration of the renewed interest in Marxist concepts displayed by contemporary American, British, and French anthropologists.